Navigating the complexities of AI-driven literary translation: Challenges and perspectives across diverse user groups - Belhassen, Saleh; Hakami, Ahmed; Alzobidy, Soleman; Hamda, Achwak (International Journal of Innovative Research and Scientific Studies, 2025)
Literary translation is an intricate process that demands linguistic skill, cultural awareness, creativity, and a comprehension of human expression. Although artificial intelligence (AI) has made significant strides in machine translation, especially concerning technical texts, its use in literary translation continues to face numerous obstacles. This paper examines the limitations of AI in conveying literary nuances such as metaphor, tone, cultural context, and stylistic features. Employing a mixed-methods approach that includes a literature review, case studies, interviews with Saudi Electronic University students (levels 7 & 8, English and Translation Department) and University of Gafsa students (Arabic Language Department, Tunisia), and SPSS analysis of survey data, this study emphasizes the discrepancies between human and machine translation within the literary field. The findings indicate that while AI can aid in activities such as generating initial drafts and conducting terminology research, it encounters difficulties with cultural subtleties, emotional richness, and stylistic accuracy. The paper concludes that AI is unlikely to supplant human translators in the near future and suggests its application as an auxiliary tool, highlighting the indispensable function of human creativity and intuition.